Long-term sensorimotor changes after a sciatic nerve block with bupivacaine and liposomal bupivacaine in a high-fat diet/low-dose streptozotocin rodent model of diabetes - Byram, Susanna C.; Lotesto, Krista M.; Volyanyuk, Michael; Exline, Jacob E.; Sager, Elizabeth A.; Foecking, Eileen M. (Frontiers in Anesthesiology, 2024)
Introduction It is unclear whether patients with diabetes are more susceptible to nerve toxicity of local anesthetics or whether nerve blocks can accelerate the progression of diabetic peripheral neuropathy. Bupivacaine is one of the most widely used local anesthetics for regional anesthesia despite many pre-clinical studies demonstrating neurotoxicity. Herein, we report the long-term functional consequences of sciatic nerve block with bupivacaine and liposomal bupivacaine (Exparel®) in an animal model of diabetes. Methods Male Sprague Dawley rats were subject to standard chow/vehicle or high-fat diet/low-dose streptozotocin to induce a diabetic phenotype. Animals were then subdivided into groups that received repeated sciatic nerve blocks of saline, bupivacaine, or liposomal bupivacaine. Mechanical allodynia and thermal hyperalgesia were assessed prior to and 12 weeks following nerve blocks utilizing the von Frey and Hargreaves tests, respectively. Exploratory and locomotor activity were assessed with open field testing, and nerve conduction velocity testing was conducted prior to the termination of the study at 28 weeks. Results Animals in the diabetic group developed sustained hyperglycemia >200 mg/dl and signs of peripheral neuropathy six weeks after treatment with streptozotocin, which persisted until the end of the study. Twelve weeks after a repeated sciatic nerve block with saline, bupivacaine, or liposomal bupivacaine, results indicate significant interaction effects of the disease group (control vs. diabetic) and local anesthetic treatment. Overall, diabetic status resulted in worse sensorimotor function compared to control animals. Treatment with perineural bupivacaine resulted in worse sensorimotor functions in both control and diabetic animals. Furthermore, bupivacaine treatment in diabetic animals with pre-existing neuropathy exacerbated sensorimotor function in some measures. In contrast, liposomal bupivacaine did not appear to cause any negative effects on functional outcomes for control or diabetic animals. Conclusion Our data indicate that bupivacaine, and not liposomal bupivacaine, causes long-term changes in tactile allodynia, thermal hyperalgesia, locomotor behaviors, and nerve conduction velocity in control as well as a high-fat diet/low-dose streptozotocin rodent model of diabetes. These results highlight the necessity to investigate safe peripheral nerve block strategies to preserve long-term functional independence in patients with or at risk for diabetic peripheral neuropathy.